1992
DOI: 10.1002/j.1460-2075.1992.tb05085.x
|View full text |Cite
|
Sign up to set email alerts
|

PDGF alpha- and beta-receptors activate unique and common signal transduction pathways.

Abstract: We have examined the signal transduction pathways of the PDGF alpha‐ and beta‐receptors, in order to characterize the specificity of each receptor type in the signaling. Porcine aortic endothelial cell lines expressing equal levels of either PDGF alpha‐ or beta‐receptors were established. The alpha‐ and beta‐receptor cells responded mitogenically to stimulation with the proper PDGF isoforms. Three aspects of actin reorganization were examined after ligand stimulation: loss of stress fibres, appearance of edge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
145
0
4

Year Published

1994
1994
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(154 citation statements)
references
References 57 publications
5
145
0
4
Order By: Relevance
“…The peptide antiserum R3, raised against the carboxyterminal tail of PDGF b-receptor, and the antiserum R7, against the PDGF a-receptor, have been described previously (Eriksson et al, 1992;Mori et al, 1993). An anti-PDGF areceptor antibody, 951, as well as antibodies against CrkII, CrkL, C3G or RasGAP were purchased from Santa Cruz Biotechnology Inc (USA).…”
Section: Antibodies and Reagentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The peptide antiserum R3, raised against the carboxyterminal tail of PDGF b-receptor, and the antiserum R7, against the PDGF a-receptor, have been described previously (Eriksson et al, 1992;Mori et al, 1993). An anti-PDGF areceptor antibody, 951, as well as antibodies against CrkII, CrkL, C3G or RasGAP were purchased from Santa Cruz Biotechnology Inc (USA).…”
Section: Antibodies and Reagentsmentioning
confidence: 99%
“…While both PDGF a-and b-receptors are able to initiate DNA synthesis (Hosang et al, 1989;Matsui et al, 1989), it has been reported that the breceptor is a more potent mediator of mitogenicity compared to the a-receptor in certain cell types (Heidaran et al, 1993;Inui et al, 1994). Moreover, whereas the b-receptor mediates stimulation of chemotaxis, a-receptor inhibits chemotaxis, at least in certain cell types (Eriksson et al, 1992;Koyama et al, 1992;Siegbahn et al, 1990). The two types of receptors also di er in their ability to mediate intracellular calcium mobilization and protein kinase C activation (Block et al, 1989;Diliberto et al, 1992;Salhany et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cellular significance of this complexity is not yet clear, but a detailed comparison of the functional activities of the a-and /?-receptors revealed similarities as well as differences. Whereas both receptors transduce a mitogenie response, only the p-receptor mediated chemotaxis and actin reorganization in the form of circular membrane ruffles [37]. Moreover, in cells having both a-and B-receptors, activation of the a-receptor inhibited B-receptor induced chemotaxis [38,39].…”
Section: Role Of Pkc-o! In ~E~~fftion Of Pi3gf Receptorsmentioning
confidence: 99%
“…[7][8][9] They are implicated in physiologic and pathologic processes, including cell growth and survival, 10 transformation, 11 migration, 12,13 vascular permeability, stroma modulation and wound healing. 14 PDGF binds selectively to receptor subunits, based on specific epitopes; 15,16 PDGF AA binds the PDGFRa, whereas PDGF AB and BB recognize both the PDGFRa and PDGFRb.…”
Section: Introductionmentioning
confidence: 99%